THE EFFECT OF VARIATION IN THE NUMBER OF SPRAYS AND DISCHARGE ON THE TECHNOLOGY SPRAY FOR EVAPORATION - Cahyo, Mei Syella Kurnia Putri; Moch Iqbal Darmawan; Srie Muljani (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2024)
Spray technology is an innovative salt production process technology that is able to increase seawater salinity and accelerate the salt production process. This study aims to determine the effect of variations in the amount of spray and discharge in spray technology on increasing seawater salinity. The experimental method was carried out by varying the spray and water discharge amount in spray technology according to the variables. This research has been successfully carried out to increase the salinity of synthetic seawater where to increase from the initial seawater salinity of 2.5 °Be to 24 °Be. It takes 16 hours taken in 3 days using the number of sprays as much as 5 sprays with a seawater flow rate of 0.2424 m³/hour in an evaporation pond of 15í—7 m. The use of the spray method proved effective in accelerating the rate of increase in salinity of synthetic seawater, which was tested to increase the salinity of synthetic seawater from 2.5 °Be to 12 °Be with an evaporation time in traditional methods of 15 days to only 11 hours. This can also happen because the temperature, humidity and wind speed were relatively stable when the research took place.